1978
DOI: 10.1126/science.199.4336.1463
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific Defense: Advantage of Social Cooperation Among Paper Wasp Foundresses

Abstract: Foundress associations and high frequencies of conspecific nest usurpation are most common where densities of Polistes metricus are high. Here nest usurpation occurs primarily in single-foundress colonies resulting in multiple-foundress colonies having significantly greater productivities than single-foundress colonies. This is not true at low densities. Conspecific pressures and not predation or parasitism provide an advantage to cooperating wasp foundresses in P. metricus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
103
0
1

Year Published

1984
1984
2013
2013

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(108 citation statements)
references
References 3 publications
4
103
0
1
Order By: Relevance
“…In all hypotheses, selective pressures from predators and parasitoids are thought to be a major promoter of social evolution (EVANS, 1977). The adaptiveness of cooperative nesting of female wasps and bees has recently been studied quantitatively (GAMBOA, 1978;LITTE, 1981;LIN, 1964;SAKAGAMI, 1977). Although SAKAGAMI and MAETA (1977) showed the adaptive significance of anti-parasitoid maternal behavior in two subsocial Ceratina bees, there was no comparable study for subsocial wasps.…”
Section: Introductionmentioning
confidence: 99%
“…In all hypotheses, selective pressures from predators and parasitoids are thought to be a major promoter of social evolution (EVANS, 1977). The adaptiveness of cooperative nesting of female wasps and bees has recently been studied quantitatively (GAMBOA, 1978;LITTE, 1981;LIN, 1964;SAKAGAMI, 1977). Although SAKAGAMI and MAETA (1977) showed the adaptive significance of anti-parasitoid maternal behavior in two subsocial Ceratina bees, there was no comparable study for subsocial wasps.…”
Section: Introductionmentioning
confidence: 99%
“…Gamboa et al (1992) and Itô and Itioka (2008) showed that the susceptibility of initial colonies in independent-founding species to the attack of predators or conspecific wasps is closely associated with the number of adults in the colony. That is, colonies that are initiated by fewer foundresses are more susceptible to attack by predators and must reduce the time to produce the first workers (Gamboa 1978;Itô and Itioka 2008;Clouse 2001).…”
Section: Duration Of the Immature Stagesmentioning
confidence: 99%
“…In general, the success of a colony is measured through the investment in individual production and the colony survival (Lorenzi and Turillazzi 1986;Reeve 1991). Gamboa (1978) observed that colonies of Polistes metricus founded by association are significantly more productive than colonies initiated by a single female. Similarly, Gamboa et al (1992) and Tibbetts and Reeve (2003) observed for P. fuscatus and P. dominulus, respectively, that colonies initiated by association are better able to defend against predators and conspecific wasps.…”
Section: Introductionmentioning
confidence: 96%
“…O sucesso das colônias, em ambas as condições climáticas, pode ser determinado pelo investimento na produção de indivíduos na população que envolve vários fatores. Trabalhos anteriores demonstram que colônias iniciadas por uma associação de fêmeas têm maior probabilidade de sucesso e maior produtividade de indivíduos, em detrimento às colônias iniciadas por uma única fêmea (Gamboa 1978;Gibo 1978;Hirose & Yamasaki 1984). Colônias com maior chance de sucesso são aquelas fundadas em ambientes rigorosamente selecionados pelas fêmeas, dessa forma, substratos que proporcionam menor variação ambiental podem ser preferencialmente escolhidos pelas fundadoras para construírem seus ninhos (Smith 2004 A fenologia das colônias foi acompanhada durante doze meses, levando-se em consideração os fenômenos de fundação, período de atividade e abandono dos ninhos.…”
unclassified